CIO and corporate strategic management changing role of CIO to CEO - Gottschalk, Petter, 1950- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book holds key information in improving a CIO's role, which would then advance his/her chances of moving into a CEO role. It provides analysis within theoretical frameworks and consulting recommendations, starting with the demand side of CEO successions, specifically highlighting approaches in IT foundations, e-business development and IT sourcing decisions"--Provided by publisher.